EP185/#391 Role of extensive processing of risk-reducing salpingo-oophorectomy specimens in BRCA1/2 germline pathogenic variant carriers. (4th December 2022) - Stroot, Iris; Brouwer, Jan; Bock, Geertruida De; Hollema, Harry; Wagner, Marise; Investigators, Hebon; Mourits, Marian; Bart, Joost
Abstract : Objectives: We assessed the importance of extensive processing of risk-reducing salpingo-oophorectomy (RRSO) specimens with regard to 1) detecting serous tubal intra-epithelial carcinoma (STIC) or high-grade serous carcinoma (HGSC) at RRSO and 2) development of HGSC in the follow-up after normal RRSO in BRCA1/2 germline pathogenic variant (gPV) carriers. Methods: From Hereditary Breast and Ovarian cancer in the Netherlands (HEBON) study, BRCA1/2 gPV carriers who underwent RRSO between 1995 and 2018 were included. Pathology reports of RRSOs were retrieved from the Dutch pathology registry and extent of processing was assessed. To confirm diagnoses of STIC/HGSC at RRSO or HGSC after normal RRSO, tissue slides of RRSO specimens with (pre)malignancy and from women who developed HGSC after RRSO were reviewed. Fisher's exact and Mann-Whitney U test were used to compare the extent of processing between the groups. Results: In total 2557 women, of which 1624 BRCA1, 930 BRCA2, and 3 with both BRCA1/2 gPV with 10.5 years of median follow-up were included. 8 isolated STICs and 30 HGSCs at RRSO were found, with 16 HGSCs after normal RRSO. Women with STIC/HGSC at RRSO more often had totally embedded fallopian tubes and ovaries (81.6 and 84.2 versus 61.1 and 65.9% respectively; p=0.01 and p=0.02). Women who did not have their RRSO specimen totally embedded had a 6 times higher risk to develop HGSC during follow-up. Conclusions: Extensive processing of RRSO specimens of BRCA1/2 gPV carriers increased detection of STIC/HGSC at RRSO and subsequently resulted in a risk-reduction for developing HGSC after normal RRSO.